2020
DOI: 10.52570/nesr.dgac2020.sr0401
|View full text |Cite
|
Sign up to set email alerts
|

Beverage Consumption and Growth, Size, Body Composition, and Risk of Overweight and Obesity: A Systematic Review

Abstract: Conclusion statements drawn as part of this systematic review describe the state of science related to the specific question examined. Conclusion statements do not draw implications, and should not be interpreted as dietary guidance. This portfolio provides the complete documentation for this systematic review. A summary of this review is included in the 2020 Advisory Committee's Scientific Report available at www.DietaryGuidelines.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 137 publications
(583 reference statements)
1
5
0
1
Order By: Relevance
“…Kids SIPsmartER was effective at reducing SSB among students and their caregivers in the rural, medically underserved Appalachian region. Our trial addresses notable gaps in the SSB intervention literature [40][41][42] and our findings are largely consistent with a recent systematic review of school-based trials that found promising results in reducing SSB among adolescents using educational/behavior interventions [40] [18][19][20][21][22][23][24][25][26][27][28]96]. These findings highlight the promise of Kids SIPsmartER as a primary prevention intervention to reduce SSB consumption.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Kids SIPsmartER was effective at reducing SSB among students and their caregivers in the rural, medically underserved Appalachian region. Our trial addresses notable gaps in the SSB intervention literature [40][41][42] and our findings are largely consistent with a recent systematic review of school-based trials that found promising results in reducing SSB among adolescents using educational/behavior interventions [40] [18][19][20][21][22][23][24][25][26][27][28]96]. These findings highlight the promise of Kids SIPsmartER as a primary prevention intervention to reduce SSB consumption.…”
Section: Discussionsupporting
confidence: 87%
“…Yet, among students consuming > 24 ounces/day there was an interesting trend whereby Kids SIPsmartER students BMI z-score appear to stabilize, on average, over the 7-month period, while the control students BMI z-scores trend upward. Exploring heterogeneity of treatment effects by baseline SSB consumption in a primary prevention intervention study is an important contribution of our study [28]; however, future fully powered studies are needed to further investigate this trend. Also, a significant treatment effect on caregivers' weight was detected, in favor of Kids SIPsmartER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, SSB consumption was found to be associated with improved cognitive function in the low and moderate intake groups but was negatively associated with higher intake levels. The Dietary Guidelines Advisory Committee in the United States have published a review in 2020 highlighting the harmful effects of high-level SSBs, by 2020, but the effect of low or moderate levels of SSB intake on health is yet to be determined ( 40 ). It has also been reported numerous times that there was no association between SSB consumption and cognitive function in children and adolescents ( 23 , 24 , 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Querschnittsstudien sind hierbei für Adipositas, [4] Typ-2-Diabetes (T2D), [5] Fettleber, [6] kardiovaskuläre Ereignisse [7] und Krebs [8] klar signifikante Risikoerhöhungen mit höherem Süßstoffgebrauch beschrieben. Auch in vielen prospektiven Studien finden sich deutliche Risikoassoziationen zu diesen Erkrankungen [9][10][11][12], während einige andere Beobachtungsstudien keine oder sogar protektive Assoziationen beschreiben [13,14]. Allerdings räumen alle Publikationen die methodischen Schwächen ihrer Arbeiten hierzu ein.…”
Section: Süßstoffe In Der Epidemiologieunclassified